O estágio supervisionado nos cursos de pedagogia da Unioeste: organização após as DCN/2015 - Kühl, Claudete Adriana Pinheiro (2022)
This research is linked to the Postgraduate Program in Education and is part of the research line Culture, Educational Processes and Teacher Training, which investigates the interrelationships between culture and education, teacher training, formal and non-formal educational processes, in their theoretical-practical, socio-political and pedagogical dimensions. The readings and discussions carried out in the Study and Research Group on Teaching, Learning and Historical-Cultural Theory - GEPEATH - contributed to the development of this work. As part of the theoretical contribution of this research, authors such as Pimenta and Lima (2006), Freire (1996), Piconez (1991), Gomes (2011), Franco (2003), Libâneo (2008) and Serrão (2006).This investigation is directed to the training of teachers and the organization of supervised training for teaching in Early Childhood Education and Early Years of Elementary School, in the Pedagogy course. The aim was to analyze how the supervised internship is organized in the Pedagogy courses at Unioeste, after the approval of the 2015 National Curricular Guidelines for Teacher Training. The educational relevance is centered on the importance of supervised training for teacher training in building the foundations of their practice. This is a qualitative research, characterized as a case study, which uses document analysis as a data source and has as its field of research the Pedagogy courses at Unioeste - Cascavel, Foz do Iguaçu and Francisco Beltrão campuses. This work is divided into three chapters, in addition of the introduction and final remarks. In the first chapter, “Pedagogy as a formative process”, we sought to understand the historical process of the Pedagogy course in Brazil and identify the legal guidelines on supervised internships in the Pedagogy course, in order to enrich the discussions and bring relevant elements to the study. In the second chapter, “Pedagogy courses at Unioeste”, the Political-Pedagogical Projects of the Cascavel, Foz do Iguaçu and Francisco Beltrão courses were analyzed. In the third chapter, “The internships in the Pedagogy courses at Unioeste”, we presented how the Supervised Internship activities are organized for the pedagogue's performance as a teacher of Early Childhood Education and Early Years in this institution, and finally, we made some considerations about categories that emerge from the internship: teaching, teaching practice, research and management. The three courses analyzed are organized to develop training work with the aim of achieving the full and integral training of education professionals, to work in teaching and management of the Brazilian educational system. As for the configuration of the Supervised Internship for teaching in Early Childhood Education and Early Years of Elementary School, these courses offer contact with the reality of the internship fields, in the different possibilities of action and intervention, opting primarily for school environments. We emphasize that Francisco Beltrão's Pedagogy course is distinguished by the workload of this discipline, based on the guidelines of the DCNFP/2015, emphasizing training in the internship for Early Childhood Education and Early Years.